Yog-nidra session and cardiovascular parameters: A Pilot study (Janaki Medical College Journal of Medical Science, 2025)
Background and Objectives: Yog-nidra is an ancient, guided meditation that has been used as instant relaxation techniques now-a-days. It is also called ‘yogic sleep’ and is gaining popularity day by day. Despite theoretical support and growing clinical interest, cardiovascular effects of Yog-nidra remains inconsistent, creating ambiguity about its therapeutic value. So here from this pilot study we tried to find the effect of Yog-nidra session on cardiovascular parametersMaterials and Methods: Heart rate (HR), Systolic blood Pressure (SBP) and Diastolic blood Pressure (DBP) were taken before and after the Yog-nidra session of 30 minutes with the help of standard digital sphygmomanometer. Data were entered and analyzed using SPSS.Results: Research-participants of this study on 30 minutes Yog-nidra session expressed that they feel relaxed, fresh and recharged after the session. They feel peace of mind and relaxation in body. Heart rate decreased from 81.77 ± 14.05 to 72.38 ± 10.76 (p